Analisis Efisiensi Biaya Operasional, Likuiditas, Dan Struktur Modal Terhadap Kinerja Pusat Investasi - Martin Kholistiana; Amalia Dewi Rahmawati; Erviana Putri Apriliany; Ferna Ririn Ananda; Rena Izza Rahmawati; Diva Syafira Maylani; Sumarno Sumarno (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The decline in Return on Assets (ROA) within the healthcare sector on the Indonesia Stock Exchange post-pandemic indicates issues regarding operational efficiency and capital management. This quantitative research aims to analyze the effect of Operating Expenses to Operating Income (BOPO), Current Ratio (CR), and Debt to Equity Ratio (DER) on the financial performance of the investment center (ROA). Using a purposive sampling method, a sample of 22 companies was selected, yielding a total of 110 observations over a 5-year observation period (2021–2025). Data were analyzed using multiple linear regression after fulfilling all classical assumption tests. The partial hypothesis testing results show that BOPO has a negative and significant effect on ROA (t=−4.912), CR has a positive and significant effect on ROA (t=4.476), and DER has a negative and significant effect on ROA (t=−4.151) with a significance value of 0.000 for all variables. Simultaneously, the contribution of the three independent variables in explaining the dynamics of ROA is 36.9% (Adjusted R Square = 0.369), while the remaining portion is influenced by other factors outside the research model. The implications of this study emphasize the importance for investment center management to reduce operating costs and control the debt proportion to maintain the stability of asset profitability.